Case Study of Geprek Bensu Franchising Disputes from Intellectual Property Legal Perspective - Urbanisasi Urbanisasi; Hartaty Halim (PT Publikasiku Academic Solution, 2023)
A trademark dispute between Benny Sujono and Ruben Onsu regarding the use of the name